Analysis of the current state of implementation of fitness clubs personnel policy - Oleksandr Aghyppo; Galina Putiatina (Kharkiv State Academy of Physical Culture, 2018)
The article analyzes the current state of implementation of the personnel policy of fitness clubs in Kharkov. The directions of reforming the system of recreational and motor activity are proposed. Purpose: to reveal the main provisions of the mechanism for the implementation of personnel policy in the system of recreational motor activity (for example, fitness clubs). Material & Methods: method of analysis of scientific literature and documentary sources, analysis of advanced domestic experience, method of system analysis, method of sociological survey, methods of mathematical statistics. The survey was conducted in order to analyze the state and prospects of development of the system of health and recreational motor activity of the population at the regional level (in particular, aspects of the implementation of personnel policy by fitness clubs). 53 respondents took part in the survey, among them 10 were representatives of the management of the physical culture and sport bodies and the "Sport for All" system, 12 were scientific and pedagogical workers, 31 were representatives of fitness clubs in Kharkiv. Results: evealed the mechanism for implementing personnel policy by fitness clubs, analyzed the state and prospects of this area of work in the field of fitness. Conclusion: as a result of the study, the functions that are performed by a competent fitness club specialist are summarized. A mechanism for the implementation of personnel policy by the subjects of the fitness industry has been formed and the principles for its implementation have been substantiated. Established priority measures to reform the fitness industry in the context of the implementation of personnel policy.